Evaluation of the anticancer activity of RIN-1, a Notch signaling modulator, in head and neck squamous cell carcinoma - Czerwonka Arkadiusz; Kałafut Joanna; Wang Shaoxia; Anameric Alinda; Przybyszewska-Podstawka Alicja; Mattsson Jesse; Karbasian Mahtab; Le Manach Doriane; Toriseva Mervi; Nees Matthias (Springer Nature, 2025)
Notch signalling is one of the key molecular pathways involved in cell-to-cell signal transduction. Although the mechanisms of action of the NOTCH receptors are already relatively well known, their biological implications remain unclear, especially during the initiation and progression of head and neck squamous cell carcinoma (HNSCC). Here, we present the growth- and differentiation-modulating effects of various "next generation" small molecule Notch modulators represented by RIN-1, and CB-103, on HNSCC, compared to gamma secretase inhibitors as "conventional" NOTCH interfering compounds, like DAPT. These molecules were tested in different cell- and tissue culture conditions represented by 2D monolayer, non-adherent or spheroid culture, 3D organoid cultures, and zebrafish in vivo model. The most pronounced, pleiotropic effects were observed for the NOTCH modulator RIN-1. At the molecular level, RIN-1-dependent activation of Notch signalling led to characteristic changes in the expression of NOTCH-regulated targets, i.e., the transcriptional suppressors HES1 and HEY1, p21 (CDKN1A) cell cycle inhibitor, and pro-apoptotic BAX markers. These changes led to restriction of proliferation, growth, and reduced motility of HNSCC cells in 2D cultures. Consequently, cell cycle arrest in the G2-M phase and induction of apoptosis were observed. Similar anticancer effects were observed in 3D cultures and in the zebrafish model. In contrast, RIN-1 treatment resulted in inhibition of Notch signalling and the growth of HNSCC spheroids under non-adherent cell culture conditions. Our results suggest that modulation of Notch signalling could be used as a chemotherapeutic agent in selected patients with intact NOTCH signaling.